Involvement of Streptomyces in the Deterioration of Cultural Heritage Materials Through Biomineralization and Bio-Pigment Production Pathways: A Review. Issue 7 (1st July 2020) - Sakr, Akmal A.; Ghaly, Mohamed F.; Edwards, H. G. M.; Ali, Mona F.; Abdel-Haliem, Mahmoud E. F.
Abstract: Streptomyces are involved in the deterioration of cultural heritage materials through several pathways, the most important of these are biomineralization and bio-pigment production. The biomineralization pathway can occur through the precipitation of calcite, silica, barytes, hydromagnesite and iron compounds on colonized paintings and on stone surfaces with paintings in relief. Streptomyces biomineralize boron although it was confirmed in biodeterioration of cultural heritage materials. The other pathway occurs via bio pigment production and the most common of these biopigments are melanin with colors ranging from black through brown to olive, carotenoids with colors ranging from red, yellow, and pink through to violet and thirdly, actinorhodin-related blue pigments.